ENVIRONMENTAL, BIOLOGICAL AND GENETIC FEATURES OF CERTAIN POPULATIONS OF GREAT GERBIL (Rhombomys opius Licht., 1823) OF KAZAKHSTAN - Kawamoto, Yoshi; Nurtazin, S.; Shevtsov, A.; Romankulov, E.; Lutsay, V.; Salmurzauly, R.; Iklasov, M.; Konysbaev, T.; Sayakova, Z.; Rysbekova, A.; Utepova, I.; Atshabar, B. (Scientific Journal of Pedagogy and Economics, 2020)
The main host of a number of especially dangerous zoonotic infections in the arid zones of Kazakhstan, covering an area of about 1.1 million km2, is the great gerbil (Rhombomys opimus). In the process of formation in natural foci of the parasitic triad (pathogen-host-vector, mutual adaptation of all its members to environmental conditions and their coevolution occurs. The article presents the results of a study of the intraspecific, population heterogeneity of ecological-biological and some genomic features of the great gerbil in three foci of zoonotic Infections: Pribalkash, Betpakdala and Predustyurt. The features of climate, soil and vegetation cover, tendencies of their perennial and seasonal changes were studied. Differences in climatic conditions and characteristics of vegetation between the 3 foci were revealed at a rather high degree of synchronization of the trend of changes in air temperature and precipitation. Analysis of the cytB gene fragment from 88 individuals from three autonomous plague foci identified 19 haplotypes that form three haplogroups, one of which is represented by individuals from the populations of two autonomous plague foci Populations of great gerbils from Kazakhstan and China are included in the same cluster and are genetically distant from the populations of Iran. Geographic isolation, significant differences in climatic, landscape, and forage conditions, microevolutionary changes in the genomic status determined the heterogeneity of three described populations of the great gerbil. A growing negative impact on the population of the great gerbil and the epizootic status of natural foci of climate warming and an increasing anthropogenic pressure, primarily in the form of overgrazing, on natural phytocenoses was noted.